The Ins and Outs of Selling Houses: Understanding Housing-Market Volatility - L. Rachel Ngai; Kevin D. Sheedy (Institute of Labor Economics (IZA), 2023)
The housing market is subject to search frictions in buying and selling houses. This paper documents the role of inflows (new listings) and outflows (sales) in explaining the volatility and co-movement of housing-market variables. An 'ins versus outs' decomposition shows that both inflows and outflows are quantitatively important in understanding fluctuations in houses for sale. The correlations between sales, prices, new listings, and time-to-sell are shown to be stable over time, while the signs of their correlations with houses for sale are found to be time varying. A calibrated search-and-matching model with endogenous inflows and outflows and shocks to housing demand matches many of the stable correlations and predicts that correlations with houses for sale depend on the source and persistence of shocks.
Keywords: E32; E22; R21; R31; 330; housing-market cyclicality; inflows and outflows; search frictions; match quality